Emergency physician attitudes towards illness verification (sick notes). Issue 1 (19th January 2021) - Hayman, Kate; McLaren, Jesse; Ahuja, Dezi; Jimenez Vanegas, Carolina; Sheikh, Hasan
Abstract: Introduction: Emergency physicians frequently provide care for patients who are experiencing viral illnesses and may be asked to provide verification of the patient's illness (a sick note) for time missed from work. Exclusion from work can be a powerful public health measure during epidemics; both legislation and physician advice contribute to patients' decisions to recover at home. Methods: We surveyed Canadian Association of Emergency Physicians members to determine what impacts sick notes have on patients and the system, the duration of time off work that physicians recommend, and what training and policies are in place to help providers. Descriptive statistics from the survey are reported. Results: A total of 182 of 1524 physicians responded to the survey; 51.1% practice in Ontario. 76.4% of physicians write at least one sick note per day, with 4.2% writing 5 or more sick notes per day. Thirteen percentage of physicians charge for a sick note (mean cost 22.50). Patients advised to stay home for a median of 4 days with influenza and 2 days with gastroenteritis and upper respiratory tract infections. 82.8% of physicians believe that most of the time, patients can determine when to return to work. Advice varied widely between respondents. 61% of respondents were unfamiliar with sick leave legislation in their province and only 2% had received formal training about illness verification. Conclusions: Providing sick notes is a common practice of Canadian Emergency Physicians; return‐to‐work guidance is variable. Improved physician education about public health recommendations and provincial legislation may strengthen physician advice to patients.